Fungsi Implementatif Tawaran Pilihan Etis-Teologis Kristen dalam Konteks Dilema Moral - Alvian Apriano (EPIGRAPHE: Jurnal Teologi dan Pelayanan Kristiani, 2019)
Mostly overtime, the ethical-theological discussion is also influenced by dilemmatic situations that cause doubts in making choices. In fact, the starting point of ethics is to consider an issue and take a stand on it without compromise with any situation in between. In this situation, questions arise about whether ethics has carried out its implementative function appropriately? With the growing firmness to making a choice, ethical-theological responsibility now requires its implementation under direction. Christian theologians notice their respective perspectives on highlighting the context of the times that creates moral dilemmas. This research seeks to offer ethical decision concepts and models when dealing with a dilemma problem in order to reawaken the firmness in ethically responding to the challenges of the times. AbstrakDekade ini, diskusi etika teologis turut dipengaruhi oleh situasi dilematis yang menyebabkan keraguan dalam menentukan pilihan. Padahal, titik tolak etika adalah mempertimbangkan sebuah persoalan dan mengambil sikap atasnya tanpa kompromi dengan situasi apa pun. Di dalam keadaan ini, muncullah pertanyaan tentang apakah etika telah menjalankan fungsi implementatifnya dengan tepat? Dengan berkembang-nya ketegasan untuk menentukan pilihan, tanggung jawab etis-teologis kini memerlukan arah implementatifnya. Para teolog etika Kristen memiliki masing-masing perspektifnya menyoroti konteks zaman yang mencip-takan dilema moral. Penelitian ini berupaya menawarkan konsep dan mo-del pilihan etis ketika berhadapan dengan sebuah persoalan dilematis guna menyadarkan kembali ketegasan dalam beretika merespons tantangan zaman.